Solvent/Detergent-Treated Plasma in the Management of Pediatric Patients Who Require Replacement of Multiple Coagulation Factors: An Open-Label, Multicenter, Post-marketing Study - Spinella, Philip C.; Borasino, Santiago; Alten, Jeffrey (Frontiers in Pediatrics, 2020)
Background: Octaplas is a solvent/detergent-treated, pooled plasma used for the management of preoperative or bleeding patients who require replacement of single or multiple coagulation factors. The aim of this study was to collect real-world data on the response to treatment with octaplas in pediatric patients. Methods: This was an open-label, multicenter, phase IV study conducted in patients <16 years old who required replacement of multiple coagulation factors due to liver dysfunction associated with coagulopathy and/or required cardiac surgery or liver surgery. Octaplas was administered intravenously based on ABO-group compatibility. The primary endpoints included the incidence of serious adverse events (SAEs), adverse drug reactions (ADRs), thrombotic events (TEs), thromboembolic events (TEEs) and hyperfibrinolytic events (HFEs). Results: A total of 50 patients were enrolled (≤2 years old, n=37; >2 years old, n=13; female, n=24) and 49 patients completed the study. Indications for the use of octaplas included planned cardiac surgery (n=40, 80.0%), liver transplant surgery (n=5, 10.0%) and liver dysfunction (n=5, 10.0%). No ADRs, HFEs or treatment-related TEs and TEEs occurred during the study. Five patients had SAEs, one of which was fatal (iatrogenic injury). Other SAEs included hemorrhage, hypotension, hemorrhagic shock, coronary artery hemorrhage, intracardiac thrombus, supraventricular tachycardia, portal vein thrombosis and respiratory failure (1 each). None of the SAEs were considered to be related to octaplas. Conclusions: Results of the present study support the use of octaplas in the management of preoperative or bleeding pediatric patients who require replacement of multiple plasma coagulation factors.